Antiviral effects of human milk oligosaccharides: A review. (November 2020) - Gao, Xiaoxiang; Wu, Desheng; Wen, Yuxi; Gao, Luying; Liu, Dan; Zhong, Ruting; Yang, Chengfeng; Zhao, Chao
Abstract: Virus infections can threaten human life and health and often cause considerable losses to society. There are multiple ways for viruses to invade host cells. Therefore, it is immensely important to inhibit the contact between virus and host cell receptors. Human milk oligosaccharides (HMOs) can not only benefit the infant brain development and the immune system enhancement, but also prevent cells from virus infections due to their similar structures with viral receptors, such as histo-blood group antigens, dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin, and sialic acid receptors. In this review, we outline the current knowledge on the complex structures of HMOs and the characteristics of infection by viruses, as well as discuss the mechanisms by which HMOs protect cells against various virus invasions.